Martensitic nucleation mechanism - 陈奇志 桑灿 吴杏芳 柯俊 (Science China. Technological sciences, 1997)
A sort of special dislocation configuration was deformation-induced in an Fe-Ni-V-C alloy by in-situ elongation tests of TEM. The cooling in-situ observations, as well as the SADPs from the region of the special dislocation configurations, proved that they are martensitic nuclei. In martensitic transformation, a nucleus changed into a small martensitic sub-plate, and a group of parallel sub-plates that formed from a group of parallel nuclei made up a big martensitic plate Martensitic transformation involved opposite shear between adjacent martensitic nuclei. By using the reduced-cell method, the crystallographic structure of observed martensitic nuclei was indexed as a face-centered orthogonal (FCO) lattice, which was explained by the nucleation mechanism proposed by the present authors. The crystallographic analysis confirmed that the defect faulting involved in martensitic nucleation took place among three close pakked planes, instead of between two adjacent planes as an ordinary stacking fault.